KNOWLEDGE, ATTITUDES AND PRACTICES OF PARENTS REGARDING ANTIBIOTIC USE IN CHILDREN - Siddiqui, Saad; Cheema, Mubeen Sultan; Ayub, Romana; Shah, Noreen; Hamza, Ameer; Hussain, Sheraz; Khan, Muhammad Hamza; Raza, Syed Musa (Journal of Ayub Medical College Abbottabad, 2014)
Background: Emerging resistance to antimicrobial chemotherapy is becoming a challenge for medicine in recent times. Un-prescribed use of antibiotics is a major contributor to development of this problem. In Pakistan access to antibiotics remains unchecked and hence results in it are over use. The aim of this study was to assess knowledge of parents regarding use of antibiotics, its associated problems, their source of information and their expectations from Paediatricians for prescription of anti-biotics. Methods: This is a questionnaire based cross sectional study conducted in Hayatabad town, District Peshawar. Parents who were consenting, had children aged between 0-16 years, and were not related to medical profession were included in study. Total number of participants interviewed was 400. Analysis was done using prevalence ratios. Results: Most of the participants were mothers. Majority of respondents were literate with education up till level of Graduation. 64% mentioned that they enjoyed a good access to healthcare. Most common source for use of antibiotics was Physician. 35% mentioned that antibiotics must be administered in any case of fever, 47% thought antibiotics to increase recovery time and 51% knew that antibiotics have their own side effect. The most common reason to administer un-prescribed antibiotics was same antibiotic being prescribed by a physician earlier followed by family member or pharmacist recommending use of antibiotic. Lack of resources was denied as a reason for self-administration of antibiotics by majority of parents. Conclusion: There is a need of intervention to increase awareness regarding judicious use of antibiotics and to check un-prescribed dispensing of antibiotics. Keywords: Parents, antibiotics, respiratory tract infections, prescription, resistance, knowledge, attitude, practices